Biodistribution and Clearance of Human Mesenchymal Stem Cells by Quantitative Three‐Dimensional Cryo‐Imaging After Intravenous Infusion in a Rat Lung Injury Model. (26th July 2016) - Schmuck, Eric G.; Koch, Jill M.; Centanni, John M.; Hacker, Timothy A.; Braun, Rudolf K.; Eldridge, Marlowe; Hei, Derek J.; Hematti, Peiman; Raval, Amish N.
Abstract : To study three‐dimensional (3D) cryo‐imaging to measure cell biodistribution and clearance after intravenous infusion, the authors established a lung injury model in rats. Human mesenchymal stem cells (hMSCs) labeled with QTracker were infused via jugular vein. Organs were cryopreserved, followed by 3D cryo‐imaging. At 60 minutes, 82 ± 9.7% of cells were detected, and at day 2, 0.06% of cells were detected. hMSCs were retained primarily in the liver, with fewer detected in lungs and spleen. Abstract : Acknowledgements: Cell tracking is a critical component of the safety and efficacy evaluation of therapeutic cell products. To date, cell‐tracking modalities have been hampered by poor resolution, low sensitivity, and inability to track cells beyond the shortterm. Three‐dimensional (3D) cryo‐imaging coregisters fluorescent and bright‐field microcopy images and allows for single‐cell quantification within a 3D organ volume. We hypothesized that 3D cryo‐imaging could be used to measure cell biodistribution and clearance after intravenous infusion in a rat lung injury model compared with normal rats. A bleomycin lung injury model was established in Sprague‐Dawley rats ( n = 12). Human mesenchymal stem cells (hMSCs) labeled with QTracker655 were infused via jugular vein. After 2, 4, or 8 days, a second dose of hMSCs labeled with QTracker605 was infused, and animals were euthanized after 60, 120, or 240 minutes. Lungs, liver, spleen, heart, kidney, testis, and intestine were cryopreserved, followed by 3D cryo‐imaging of each organ. At 60 minutes, 82% ± 9.7% of cells were detected; detection decreased to 60% ± 17% and 66% ± 22% at 120 and 240 minutes, respectively. At day 2, 0.06% of cells were detected, and this level remained constant at days 4 and 8 postinfusion. At 60, 120, and 240 minutes, 99.7% of detected cells were found in the liver, lungs, and spleen, with cells primarily retained in the liver. This is the first study using 3D cryo‐imaging to track hMSCs in a rat lung injury model. hMSCs were retained primarily in the liver, with fewer detected in lungs and spleen. Effective bench‐to‐bedside clinical translation of cellular therapies requires careful understanding of cell fate through tracking. Tracking cells is important to measure cell retention so that delivery methods and cell dose can be optimized and so that biodistribution and clearance can be defined to better understand potential off‐target toxicity and redosing strategies. This article demonstrates, for the first time, the use of three‐dimensional cryo‐imaging for single‐cell quantitative tracking of intravenous infused clinical‐grade mesenchymal stem cells in a clinically relevant model of lung injury. The important information learned in this study will help guide future clinical and translational stem cell therapies for lung injuries.